Functions and Continuity

Calculus Level 4

f ( x ) = { a ( 1 x sin x ) + b cos x + 5 x 2 if x < 0 3 if x = 0 ( 1 + ( c x + d x 3 x 2 ) ) 1 x if x > 0 f(x)= \begin{cases} \dfrac{a(1-x\sin x) + b\cos x + 5}{x^2}&\text {if } x<0\\ 3& \text{if }x=0\\ \left(1+\left(\dfrac{cx + dx^3}{x^2}\right)\right)^{\frac 1 x} & \text{if }x>0 \end{cases}

A piecewise function f ( x ) f(x) is defined as shown above, where a , b , c a,b,c and d d be constants.

If f ( x ) f(x) is continuous at x = 0 x=0 , find 2 e d + 7 c 3 a 5 b 2e^d + 7c-3a-5b .

Clarification : e 2.71828 e \approx 2.71828 is the Euler's number .


The answer is 29.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
May 24, 2016

Relevant wiki: Maclaurin Series

For f ( x ) f(x) to be continuous at x = 0 x=0 , lim x 0 f ( x ) = lim x 0 + f ( x ) = f ( 0 ) = 3 \implies \displaystyle \lim_{x \to 0^-} f(x) = \lim_{x \to 0^+} f(x) = f(0) = 3 .

f ( x ) = a ( 1 x sin x ) + b cos x + 5 x 2 By Maclaurin series = 1 x 2 [ a ( 1 x ( x x 3 3 ! + x 5 5 ! . . . ) ) + b ( 1 x 2 2 ! + x 4 4 ! . . . ) + 5 ] = a x 2 a + a x 3 ! a x 3 5 ! . . . + b x 2 b 2 ! + b x 2 4 ! . . . + 5 x 2 \begin{aligned} f_-(x) & = \frac{a(1-x\color{#3D99F6}{\sin x}) + b\color{#3D99F6}{\cos x} + 5}{x^2} \quad \quad \small \color{#3D99F6}{\text{By Maclaurin series}} \\ & = \frac{1}{x^2}\left[a\left(1-x\color{#3D99F6}{\left(x - \frac{x^3}{3!} + \frac{x^5}{5!} - ... \right)}\right) + b\color{#3D99F6}{\left(1 - \frac{x^2}{2!} + \frac{x^4}{4!} - ... \right)} + 5\right] \\ & = \frac{a}{x^2} - a + \frac{ax}{3!} - \frac{ax^3}{5!} - ... + \frac{b}{x^2} - \frac{b}{2!} + \frac{bx^2}{4!} - ... + \frac{5}{x^2} \end{aligned}

For f ( 0 ) = 3 f_-(0) = 3 ,

{ a + b + 5 = 0 a b 2 = 3 b = 4 a = 1 \implies \begin{cases} a+b+5 = 0 \\ - a - \dfrac{b}{2} = 3 \end{cases} \color{#D61F06}{\implies b = -4 \implies a = -1}

f + ( x ) = ( 1 + ( c x + d x 3 x 2 ) ) 1 x = ( 1 + ( c x 2 + d 1 x ) ) 1 x For f + ( 0 ) to converge when x 0 + , c = 0 = [ ( 1 + 1 1 d x ) 1 d x ] d \begin{aligned} f_+(x) & = \left(1+\left(\dfrac{cx + dx^3}{x^2}\right)\right)^{\frac 1 x} \\ & = \left(1+\left(\dfrac{\color{#3D99F6}{\frac{c}{x^2}} + d}{\frac{1}{x}}\right)\right)^{\frac 1 x} \quad \quad \small {\color{#3D99F6}{\text{For }f_+(0) \text{ to converge when } x \to 0^+,}} \ \color{#D61F06}{c = 0} \\ & = \left[ \left(1+\dfrac{1}{\frac{1}{dx}} \right)^{\frac 1 {dx}} \right]^d \end{aligned}

For f + ( 0 ) = 3 f_+(0) = 3 ,

f + ( 0 ) = lim x 0 + [ ( 1 + 1 1 d x ) 1 d x ] d = e d = 3 d = ln 3 \begin{aligned} \implies f_+(0) & = \lim_{x \to 0^+} \left[ \left(1+\dfrac{1}{\frac{1}{dx}} \right)^{\frac 1 {dx}} \right]^d \\ & = e^d = 3 \\ \color{#D61F06}{\implies d} & \color{#D61F06}{= \ln 3} \end{aligned}

Therefore, 2 e d + 7 c 3 a 5 b = 2 e ln 3 + 7 ( 0 ) 3 ( 1 ) 5 ( 4 ) = 6 + 0 + 3 + 20 = 29 2e^d + 7c - 3a - 5b = 2e^{\ln 3} + 7(0) - 3(-1) - 5(-4) = 6+0+3+20 = \boxed{29}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...